Value creation and capture in innovation ecosystems: an analysis in platform and territorial perspectives - Santos, Carlos Alberto Frantz dos (2024)
The literature on innovation ecosystems has been widely recognized for its ability to assist companies in creating new business opportunities, and to facilitate the development and enhancement of the innovation projects in diverse geographical regions. For this reason, value creation and capture have been considered a central issue in the field of innovation ecosystem studies. However, creating and capturing value within an innovation ecosystem from the perspective of a company is substantially different from that within a territorial innovation ecosystem. Regardless of the type of innovation ecosystem, managing the value creation and capture process is a challenge. To contribute to this discussion, this thesis aims to analyze how value creation and capture occur in innovation ecosystem from the platform and territorial perspectives. Three primary theoretical gaps have been identified concerning the relationship between value creation, value capture, and innovation ecosystems: firstly, the need to comprehensively understand how these processes unfold within the context of innovation ecosystems; secondly, the distinction in value creation and capture between territorial and platform perspectives; and finally, the relatively unexplored context of value creation and capture within innovation ecosystems of emerging countries. To address these gaps, a qualitative approach was employed. This thesis comprises three distinct papers: a theoretical essay, a systematic literature review, and a comparative case study. The first paper, ‘Value Creation and Capture in Innovation Ecosystems’, aimed to propose an integrative framework for analyzing the creation and capture of value in innovation ecosystems. The second paper ‘Creating and Capturing Value in Innovation Ecosystems: a systematic literature review between 2010 and 2021’ aims to identify what are the contributions of the platform and territorial perspectives to the literature on value creation and capture in innovation ecosystems. The third paper, 'Developing Innovation Ecosystems Through Value Creation and Capture Mechanisms: a comparative case study of platform and territorial perspectives,' aimed to analyze value creation and capture mechanisms in both territorial and platform innovation ecosystems. This comparative case study was conducted in two innovation ecosystems within an emerging country context, situated in the Serra Gaúcha region of Southern Brazil. The findings suggest that the competitive pursuit of value capture undermines the process of value creation, consequently reducing the innovation ecosystem development. Therefore, innovation ecosystem managers need to comprehend the crucial aspect of an integrated view of value creation and capture mechanisms when establishing their ecosystem strategies. The results underscore that aligning objectives to establish a value proposition among actors within the quadruple helix is more complex in territorial innovation ecosystems than in platform innovation ecosystems. This underscores the inherent complexity of engaging actors in aligning their interests within territorial innovation ecosystems, given their different value perceptions, diverse value capture mechanisms, and distinct critical success factors, which differ from the platform perspective. Finally, the results describe an emerging economy region characterized by industries of low and medium technological intensity. Consequently, the findings contribute to delineating the challenges encountered by companies situated outside metropolitan areas, organizations undergoing a transformative shift in their innovation culture, and actors possessing cultural traits that initially impede innovation adoption. This is particularly pertinent for traditional or family-owned enterprises that have yet to embrace an innovation-driven culture, as observed in numerous emerging countries regions.